(untitled) (Andamios, Revista de Investigación Social, 2012)
The links between political parties and civil society with democracy are real, but difficult and problematic. This essay analyzes the paradoxes and democratic reversals of these political actors. Democracy needs it’s convergence, but also of a State that defines certain social conditions.